Coil Occlusion of Coronary Cameral Fistula: A Case Report - Begum, NNF; Haque, AFM Shamsul; Rahman, MF (Cardiovascular Journal, 2011)
Congenital coronary artery fistula is a rare anomaly that can cause several types of morbidity and mortality. Interventional occlusion of coronary artery fistula has become a well-accepted alternative to surgical therapy. A coronary cameral fistula originating from right coronary artery (RCA) and draining to right atrium (RA) was occluded with a detachable coil in a two years old girl in catheterization laboratory of Combined Military Hospital (CMH) Dhaka. This is the first ever case of coil occlusion of coronary cameral fistula in Bangladesh, which led to the writing of this report. Keywords: Coronary Cameral Fistula; Coil occlusion. DOI: http://dx.doi.org/10.3329/cardio.v3i2.9192 Cardiovasc. J. 2011; 3(2): 218-221